Clinical, myopathological, and genetic features of two Chinese families with Andersen-Tawil syndrome - Wang, Jiaxuan; Qu, Qianqian; Zheng, Xianzhao; Ma, Xiaoli; Cui, Wenhao; Lv, Zheng; Hu, Cong; Li, Shiyao; Zhao, Jiongbo; Lv, Haidong (Frontiers in Neurology, 2024)
Purpose: To explore the clinical, muscle pathological, and pathogenic gene mutation characteristics of Andersen-Tawil Syndrome (ATS) and enhance the understanding of ATS among clinical practitioners. Methods: Retrospective analysis of clinical data and muscle pathology of two ATS families, along with genetic testing for probands and some family members. Results: In Family 1, spanning four generations, four individuals were affected, while Family 2 had two affected individuals across four generations. All six patients in both families experienced onset in childhood, presenting with periodic paralysis, arrhythmias, and craniofacial skeletal abnormalities.Physical examination revealed characteristic features in six patients: small mandible, wide eye spacing, and fifth-digit clinodactyly. Four adult patients were shorter in stature, while the growth status of a pediatric patient was indeterminate. The long exercise tests were positive in both probands. Muscle MRI showed no significant abnormalities, but muscle pathology revealed rimmed vacuoles and tubular aggregates. Genetic testing identified KCNJ2 gene mutations in two probands and some of their family members, c.407C>T (p.S136F) and c.652C>T(p.R218W) heterozygous mutation respectively. Conclusion: Among the clinical symptoms of the patients with Andersen-Tawil Syndrome in this study, not everyone exhibits the full triad of signs: periodic paralysis is the most common initial symptom, craniofacial and digit skeletal abnormalities are characteristic signs, and ventricular arrhythmias pose the most serious potential risk. Given that these typical symptoms were observed in 5 out of 6 patients, clinicians should pay special attention to these typical symptoms, and patients with these symptoms should be followed up over time. Muscle biopsy may reveal pathological changes such as tubular aggregates, but genetic testing for KCNJ gene mutations remains a crucial diagnostic criterion for this syndrome.